2016
DOI: 10.1089/acm.2015.0276
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Thermal Therapy with Indirect Moxibustion Decreases Renal Arterial Resistive Index in Patients with Chronic Kidney Disease

Abstract: Renal vascular resistance was decreased after indirect moxibustion therapy in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The moxibustion on the acupoints at the vertex cranii of insomnia patients yields a curing rate of 90.9% for insomnia [ 33 ]. Indirect moxibustion can decrease the renal vascular resistance in patients with chronic kidney disease [ 34 ]. According to previous studies of moxibustion efficacy and the mechanism of photobiological effect, the relationship between moxibustion effects and SC was analyzed; it was inferred that the more extensive biological effects of moxibustion are intimately linked with the near infrared radiation of moxibustion.…”
Section: Discussionmentioning
confidence: 99%
“…The moxibustion on the acupoints at the vertex cranii of insomnia patients yields a curing rate of 90.9% for insomnia [ 33 ]. Indirect moxibustion can decrease the renal vascular resistance in patients with chronic kidney disease [ 34 ]. According to previous studies of moxibustion efficacy and the mechanism of photobiological effect, the relationship between moxibustion effects and SC was analyzed; it was inferred that the more extensive biological effects of moxibustion are intimately linked with the near infrared radiation of moxibustion.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the limitation of invasiveness, acupuncture seems to induce a high risk of infection in patients with CKD whose immunity is often impaired [12]. e clinicians, therefore, turned their attention to moxibustion, a local thermotherapy on acupoints that burns moxa cones or sticks, to generate a warming stimulation [13]. Moxibustion provides a safer therapeutic effect than acupuncture by comprehensively delivering the medicinal effect of moxa, thermal and light radiation effect of burning of moxa, and aromatherapeutic effect of the combustion products of moxa [14].…”
Section: Introductionmentioning
confidence: 99%
“…Paterno et al [12] reported that electroacupuncture and moxibustion had beneficial effects on chronic kidney disease by decreasing the renal sympathetic nerve activity leading to lowered blood pressure. In particular, Matsumoto-Miyazaki et al [13] evaluated the moxibustion treatment on renal hemodynamic and found a reduction of renal vascular resistance after indirect moxibustion due to autonomic nervous system modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The sympathetic nervous system is a branch of autonomic nervous system and plays a crucial role in the control of the cardiovascular system in humans through the regulation of both cardiac function and peripheral blood flow. Moxibustion has been reported to reduce sympathetic nerve activity in the treatment of chronic kidney disease [12, 13]. However, moxibustion has also been found to excite the activity of muscle sympathetic fibres [9].…”
Section: Introductionmentioning
confidence: 99%